Development of a PBL-based differentiated e-module to improve mathematical problem-solving skills of fifth grade elementry school - Anita Zunarni; Mohammad Zainuddin; Slamet Arifin; Intan Sari Rufiana (Universitas Kanjuruhan Malang, 2026)
This study aimed to develop a differentiated e-module based on the Problem-Based Learning (PBL) model to improve mathematical problem-solving skills among fifth-grade elementary students. The study employed a Research and Development (R&D) approach using the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Participants included fifth-grade students and teachers in Blitar. The e-module was validated by material experts, media experts, and practitioners, and tested through small-group (6 students) and large-group (28 students) trials. Data were collected using validation sheets, questionnaires, and pretest–posttest instruments. Results showed high validity, with scores of 89% from material experts and 88% from media experts, while practicality reached 92%, indicating a very practical product. Effectiveness testing revealed improved student performance (mean pretest = 55.40; mean posttest = 80.20), supported by a significant paired t-test result (p = 0.000 < 0.05). The e-module effectively supports adaptive, student-centered mathematics learning.